A METHOD FOR DETERMINING LOCATION OF VOLTAGE FLUCTUATIONS SOURCE IN ELECTRIC GRID - G.A. Senderovich (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. The purpose of work is development of a method of definition of the location of a source of fluctuations of voltage. Methodology. The reasons of emergence of fluctuations of voltage at an arrangement of a source both in power lines, and in the consumer's networks, are connected with changes of consumption and active and reactive capacities. As criterion for definition of the location of a source of fluctuations of voltage we choose change of size of the active power received by reception substation on equivalent communication with system. The source of fluctuations of voltage is external for the consumer if emergence of fluctuations of voltage leads to the coordinated changes of tension and consumed in the area of active power that corresponds to a condition of the positive regulating effect of active loading on voltage (1). The source of fluctuations of voltage is internal for the consumer if emergence of fluctuations of voltage leads to counter changes of tension and consumed in the area of active power that resembles a condition of the negative regulating effect of active loading on voltage superficially (6). Results. The method of definition of the location of a source of fluctuations of voltage in an electric network which, works by the principle of an assessment of correlation of change of power and tension in a power supply network is developed. The method allows to consider shift between extrema of curves of change of voltage of U(t) and power of Pload(t). Originality. The method of definition of an arrangement of a source of fluctuations of voltage is developed. Practical value. The answer to this question where the source of fluctuations of voltage (in the territory of the consumer is located or in an external network) confirmed with the determined calculation, can form a basis of the expert opinion for the solution of legal disputes at an assessment of the damages caused by poor quality of electric energy.